2012
DOI: 10.1096/fj.12-222216
|View full text |Cite
|
Sign up to set email alerts
|

Increased oxidized low‐density lipoprotein causes blood‐brain barrier disruption in early‐onset preeclampsia through LOX‐1

Abstract: Early-onset preeclampsia (EPE) is a severe form of preeclampsia that involves life-threatening neurological complications. However, the underlying mechanism by which EPE affects the maternal brain is not known. We hypothesized that plasma from women with EPE increases blood-brain barrier (BBB) permeability vs. plasma from women with late-onset preeclampsia (LPE) or normal pregnancy (NP) and investigated its underlying mechanism by perfusing cerebral veins from nonpregnant rats (n=6-7/group) with human plasma f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
69
3
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(75 citation statements)
references
References 52 publications
2
69
3
1
Order By: Relevance
“…Circulating factors have shown to increase BBB permeability and seizure activity 17, 18 . For example, preeclampsia is associated with an superimposed dyslipidemia compared to normal pregnancy 29, 30, 31 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Circulating factors have shown to increase BBB permeability and seizure activity 17, 18 . For example, preeclampsia is associated with an superimposed dyslipidemia compared to normal pregnancy 29, 30, 31 .…”
Section: Discussionmentioning
confidence: 99%
“…For example, preeclampsia is associated with an superimposed dyslipidemia compared to normal pregnancy 29, 30, 31 . Recent studies demonstrated that elevated levels of oxLDL increase BBB permeability and may be an important contributor to vasogenic brain edema in severe early-onset preeclampsia 17, 32 . Our results suggest that antepartum eclampsia occurs more often in early-onset preeclampsia, however, did not indicate that eclamptic women already had an underlying metabolic disorder.…”
Section: Discussionmentioning
confidence: 99%
“…Several lines of evidence have suggested that oxLDL exhibits a wide range of biological effects on cultured cells. Increased circulating levels of oxLDL in PE have been shown in several [30,31], but not all studies [32]. LOX-1 is an endothelial receptor for circulating oxLDL and has been studied extensively in pathological states such as atherosclerosis, diabetes, coronary arterial heart disease, and hypertension [33].…”
Section: Discussionmentioning
confidence: 99%
“…[44][45][46] These modified particles are cytotoxic to all retinal cell types, including capillary cells in the BRB (thus creating a positive feedback process in which transient leakiness of the BRB leads to chronic damage). 40,41,[47][48][49][50] Thus, serum lipid profile may be less important, and weakening of the BRB may be a prerequisite for local lipoprotein-mediated damage.…”
Section: Supportive Evidence For the Role Of Apolipoproteinsmentioning
confidence: 99%